The effect of coagulants and antiscalants discharged with seawater desalination brines on coastal microbial communities: A laboratory and in situ study from the southeastern Mediterranean. (1st March 2017) - Belkin, Natalia; Rahav, Eyal; Elifantz, Hila; Kress, Nurit; Berman-Frank, Ilana
Abstract: Desalination outflows frequently discharge brine containing coagulants and antiscalants (e.g. Iron-hydroxides and polyphosphonates) to the coastal environment. Here we examined changes in composition and productivity of natural microbial coastal communities in experimental mesocosms treated with either iron-hydroxide (Fe), polyphosphonate (Pn), or a combination of high salinities with both chemicals (All). Within 2 h of addition Fe already altered the microbial community composition, enhanced the bacterial production (BP) and cell specific production (BP/BA), and decreased primary production. Addition of Pn, relieved phosphorus stress as demonstrated by the immediate (within 2 h) and significant reduction in the ecto-enzyme alkaline phosphatase activity (APA). Synergistic effects were observed in the All treatment, reflected by increased production of both primary and bacterial producers as P-stress was relieved. After 10 days of incubation, the microbial community composition changed significantly only in the All treatment. The Fe-only treatment caused a significant decline in autotrophic biomass and in the assimilation number (AN), while in both the Pn and the All treatments the BP/BA increased with the added P. We also examined the microbial community responses in a natural impacted environment at the Ashkelon seawater desalination plant brine discharge site during summer and winter. The community composition differed in elevated-salinity compared with non-impacted stations with higher AN and bacterial efficiencies (BP/BA) measured in summer in the elevated-salinity stations. The seasonal differences in responses may reflect both biotic (i.e. initial community composition) and abiotic factors (currents and residence time of salinity gradients). Our results emphasize that desalination brine discharges that include chemicals such as iron-hydroxide and polyphosphonates can induce physiological and compositional changes in the microbial community. With the expansion of desalination facilities worldwide such shifts in composition and function of the microbial communities may destabilize and change local aquatic food webs and should thus be monitored. Highlights: SWRO brine, Fe-hydroxide, & phosphonate impact microbial physiology & composition. Fe-hydroxides immediately reduced microbial production & biomass. Brine, phosphonates, & Fe-hydroxides altered production and composition after 10 d. At SWRO facility, high salinity sites impacted microbial composition during summer & winter.